Evaluation of Dialysis Efficiency for Renal Failure Patients in Libya's Southern, Ubari Region (Journal of Medical Sciences, 2022)
Kidney disease is one of the most common causes of kidney failure in the world. Dysfunctional kidneys cannot effectively eliminate harmful toxins and maintain normal body functions. To eliminate accumulated toxins, individuals suffering from this condition undergo hemodialysis or peritoneal dialysis. This study aimed to evaluation of the effectiveness of dialysis in removing toxins, as well as the effects of hemodialysis on electrolytes and biochemical substances. Method: 24 haemodialysis patients were recruited from the Ubari region in the south of Libya. Blood samples were collected before and after dialysis and analysis of blood biochemical, haemotoligical and electrolytes  parameters. In each patient, the average concentrations of these parameters and the rate of urea decline were calculated. Results: It showed in Al-Tanahma Dialysis Unit,  WBC and MCHC, urea, creatinine, uric acid, and potassium concentrations were significantly different (P